Selective Couplers Based on Multiplexed Volume Holographic Gratings for Waveguide Displays - Maria Shishova; Alexander Zherdev; Sergey Odinokov; Vladimir Venediktov; Dmitrii Lushnikov; Yohan Kim (Photonics, 2021)
Diffraction waveguides are widely used in augmented reality devices as information display systems for the introduction of data into the human visual field in order to supplement information about the world around us. This paper formulates the principles of radiation conversion in diffraction waveguides made of photo-thermo-refractive glass on the basis of multiplexed volume holographic gratings, and the advantages and disadvantages of high spectral-angular selectivity are analyzed. In the optical scheme, each of the superimposed volume holographic gratings in the diffraction waveguide forms a corresponding part of the composite angular field of view of the augmented reality device. A proposed mathematical model based on angular multiplexing made it possible to synthesize the diffraction optical element for a new type of diffraction waveguide made from photo-thermo-refractive glass and to create a prototype with an angular resolution of at least 3.0 ± 0.5′, with a brightness change in the image of less than 20% and with a composite angular field of view of 32°.